PEMANFAATAN SISTEM INFORMASI UNTUK MENINGKATKAN KUALITAS MANAJEMEN DALAM MEMBUAT PERENCANAAN INVESTASI - Rachmawati, Susan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
Financial reporting is important for a company engaged in the business of profit or business or non profit business or non business due to the financial statements containing historical information i.e. information penyajikan has happened giving rise to gaps in information needs therefore required an analysis of the financial statements in order to overcome that gap by means of processing the information so that it can help the decision makers do forecasts relating to the future of them by using liquidity ratio (analysis , solvency, profitability). The financial statements can be used for planning investment. Research methods used are secondary data and decision making based on the existing description. The result is a performance that exists inside already quite well with the increased liquidity ratio, activ ity, turnover, return on assets, return on equity, growth and the decrease in the ratio of solvency assessment, as well as the existence of a performance management less well seen from the decrease in the net profit margin. Investment planning can also be done through the existing data in the financial statements profit and loss balance sheet in particular through depreciation and amortization and earnings withheld.